Respuesta :

Answer:

7)  y⁹

9)  a⁸

Step-by-step explanation:

when we multiply two exponents (of the same base), we can add them

so, a² · a³ = a² ⁺ ³ = a⁵

let's test it out!

(a = 2 in our example)

2² · 2³ = 2⁵

4 · 8  = 32   (2⁵ = 32)

32 = 32

because this is true, we know that we can add exponents of the same base when multiplying them together

now, let's try out the question at hand:

y³ · y⁶

well, we know that 3 + 6 = 9, so y³ · y⁶ can be simplified to y

--

now, we're going to be working with division. We know that division is the inverse of multiplication, so we logically know that instead of adding exponents, we subtract them when dividing

here,

a³ ÷ a² would equal a¹    (3 - 2 = 1)

let's put a = 2 again:

a³ ÷ a² = a³ ⁻ ² = a¹ = a

2³ ÷  2² =   2¹

8  ÷   4   =  2

2   =  2

once again, we have proven this shortcut to be true

now, to the problem at hand!

first, we can multiply a³ · a⁹

a³  ·  a⁹   =  a³ ⁺ ⁹  =  a¹²

so, let's rewrite the problem:

a¹² /  a⁴

because we're dividing with exponents, we can subtract 12 - 4

a¹² / a⁴

a¹² ÷  a⁴

a¹² ⁻ ⁴

a⁸

so, our simplified answer is a

(note: they must be the same base, [the thing that the exponent is attached to] for this to apply)

hope this helps (and makes sense)! have a lovely day :)

The required simplification is   [tex]y^{9}[/tex]  and  [tex]a^{8}[/tex] .

To simplify the following 1 )  [tex]y^3* y^6[/tex]  2 ) [tex]\frac{a^3*a^9}{a^4}[/tex].

What is simplification?

The process in mathematics to operate and interpret the function to make the function simple or more understandable is called simplifying and the process is called simplification.

1 )  [tex]y^3* y^6[/tex]
= [tex]y^3* y^6[/tex]
since the base of the exponents is the same so the powers of y get added
[tex]=y^{3+6}[/tex]
[tex]=y^{9}[/tex]

2 ) [tex]\frac{a^3*a^9}{a^4}[/tex]
[tex]=\frac{a^3*a^9}{a^4}[/tex]
since the base of the exponents is the same so the powers of a get added in the numerator.
[tex]=\frac{a^{3+9}}{a^4}[/tex]
[tex]=\frac{a^{12}}{a^4}[/tex]
Now, the power of the numerator will get decreased by the power of the denominator because the base is common i.e. a
[tex]=a^{12-4}[/tex]
[tex]=a^{8}[/tex]

Thus the required simplification is   [tex]y^{9}[/tex]  and  [tex]a^{8}[/tex] .

Learn more about simplification here: https://brainly.com/question/12501526

#SPJ5

ACCESS MORE